2014
DOI: 10.22610/imbr.v6i2.1103
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Human Capital on the Organization’s Innovative Capabilities: Case of Telecom Sector in Pakistan

Abstract: The purpose of this study is to investigate the impact of human capital on organization’s innovative capabilities in the narrative context of Pakistan. Today various organizations recognized the significance and importance of the intellectual capital. Without any doubt in knowledge-intensive organizations like telecom sector organizations intellectual capital plays a vital role in the contemporary aggressive and everchallenging business environment. The organizations can achieve competitive edge over its com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…Organizational innovation needs an agile workforce to identify innovation opportunities and providing new and innovative ideas. The findings of this study are additionally confirmed by Khodabandeh et al (2018), Khan et al (2014), Munteanu et al (2020), Doz (2020), Azizsafaei (2017), Sabahi and Parast (2020), Diaz-Fernandez et al (2017), Abili et al (2015), Ziaee et al (2012), Zahedi et al (2013), Abrisham Kar and Abdollahi (2016) that believed that there is a positive relationship among the human resources, HRA and the innovation of the new product and also, employee and organizational innovation. Finally, this study concluded that HRA played a mediating role in this positive relationship between self-development and organizational innovation.…”
Section: Discussionsupporting
confidence: 83%
“…Organizational innovation needs an agile workforce to identify innovation opportunities and providing new and innovative ideas. The findings of this study are additionally confirmed by Khodabandeh et al (2018), Khan et al (2014), Munteanu et al (2020), Doz (2020), Azizsafaei (2017), Sabahi and Parast (2020), Diaz-Fernandez et al (2017), Abili et al (2015), Ziaee et al (2012), Zahedi et al (2013), Abrisham Kar and Abdollahi (2016) that believed that there is a positive relationship among the human resources, HRA and the innovation of the new product and also, employee and organizational innovation. Finally, this study concluded that HRA played a mediating role in this positive relationship between self-development and organizational innovation.…”
Section: Discussionsupporting
confidence: 83%
“…This argument strongly emphasizes the significance of investing in these intangible and intricate to emulate assets, like social capital. Social capital is a knowledge resource that is utilized by the organization to achieve the competitive advantage and success (Khan et al, 2014;Yasir and Majid, 2019). Social capital is the outcome of the interactions and collaborations between the people or groups who share their ideas; in this context, social capital can be defined as assets generated by interpersonal networks which are, therefore, embedded and available within them (Subramaniam and Youndt, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In modern era, the growing significance of social capital has prompted a large number of studies related to its antecedents and outputs like innovativeness (Subramaniam and Youndt, 2005), competitive advantage (Nahapiet and Ghoshal, 1998) and value creation (Khan et al, 2014). Still there is lack of empirical examinations that how social capital augments the strategic renewal of organizations in developing economies.…”
Section: Introductionmentioning
confidence: 99%